1986
DOI: 10.1056/nejm198609113151103
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antibodies against Fetal Cardiac Antigens in Congenital Complete Heart Block

Abstract: An immunologic basis for congenital heart block has been proposed previously. To investigate the association between congenital heart block and maternal antibodies capable of crossing the placenta, we used immunofluorescence to examine serum samples from 41 mothers and 8 affected children, together with serum from controls, for antibodies to fetal cardiac tissue. Twenty-one mothers (51 percent) had IgG antibody reactive with fetal heart tissue, as compared with only 9 of 94 controls (10 percent; P less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(60 citation statements)
references
References 17 publications
0
56
0
4
Order By: Relevance
“…Antibodies to SS-A/Ro and SS-B/La ribonucleoproteins in maternal sera have been almost universally demonstrable when neonatal lupus is identified in a child (4)(5)(6). These autoantibodies are found with high frequency in the sera of individuals with Sjogren's syndrome (SS) or systemic lupus erythematosus (SLE), in some of their clinically normal relatives, and occasionally in otherwise healthy individuals (7,8).…”
Section: )mentioning
confidence: 99%
“…Antibodies to SS-A/Ro and SS-B/La ribonucleoproteins in maternal sera have been almost universally demonstrable when neonatal lupus is identified in a child (4)(5)(6). These autoantibodies are found with high frequency in the sera of individuals with Sjogren's syndrome (SS) or systemic lupus erythematosus (SLE), in some of their clinically normal relatives, and occasionally in otherwise healthy individuals (7,8).…”
Section: )mentioning
confidence: 99%
“…It has been suggested that CCHB is a model of passively acquired autoimmune injury as a consequence of pathogenic maternal autoantibodies [4]. The reactivity between anti-Ro/SS-A antibodies and fetal cardiac tissue including the conduction system have been shown [5,6], as well as the presence of 52 kD and 60 kD Ro/SS-A and La/SS-B antigen in fetal heart tissue [7]. Alexander et al [8] have reported the inhibition of cardiac repolarization by anti-Ro/SS-A in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart block {CHB), a potentially fatal and irreversible disease of infants, has been suggested as a consequence of transplacental passage of maternal autoantibodies to the small ribonucleoproteins La/SS-B and Ro/SS-A (1)(2)(3). La (48 kD) is thought to be either a nuclear transcription termination factor (4], and/or a cytoplasmic protein capable of ATPdependent melting of RNA/DNA hybrids [5], Ro (52 or 60 kD) is a cytoplasmic antigen, whose precise biological function is unknown, Autoantibodies to Ro and La are found in autoimmune diseases such as primary Sjogren's syndrome (SS) or secondary Sjogren's syndrome accompanied by systemic lupus erythematosus (SLE) [6,7].…”
Section: Introductionmentioning
confidence: 99%